Aplastic Anemia with Ethosuximide - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
An 8-year-old girl who developed aplastic anemia after 8 months ethosuximide therapy for absence seizures is reported from the Children's Medical College of Virginia, Richmond, VA.